Protein Timing Does Not Affect Next-Day Recovery of Strength or Power but May Enhance Aerobic Adaptations to Short-Term Variable Intensity Exercise Training in Recreationally Active Males: A Pilot Study - Hannaian, Sarkis J.; Orlando, Mark N.; Abou Sawan, Sidney; Mazzulla, Michael; West, Daniel W. D.; Moore, Daniel R. (Frontiers in Sports and Active Living, 2020)
BACKGROUND: Variable intensity training (VIT) characteristic of stop-and-go team sport exercise may reduce performance capacity when performed on successive days but also represent a strategy to induce rapid training-induced increases in exercise capacity. Although post-exercise protein enhances muscle protein synthesis, the timing of protein ingestion following variable intensity training (VIT) on next-day recovery and short-term performance adaptation is unknown. PURPOSE: To determine if immediate (IMM) as compared to delayed (DEL) protein ingestion supports greater acute recovery of exercise performance during successive days of VIT and/or supports chronic training adaptations. METHODS: Sixteen habitually active men performed five consecutive days of variable intensity training (VIT) in the evening prior to consuming a beverage providing carbohydrate and whey protein (IMM; 0.7g and 0.3g/kg, respectively) or carbohydrates alone (DEL; 1g/kg) with the reciprocal beverage consumed the following morning. Performance was assessed before each VIT (recovery) and two days after the final VIT (adaptation). RESULTS: Five consecutive days of VIT progressively decreased anaerobic peak power ( 7%) and muscle strength (MVC; 8%) with no impact of protein timing. Following 2 days of recovery, VIT increased maximal voluntary contraction and predicted VO2peak by 10% and 5%, respectively, with a moderate beneficial effect of IMM on predicted VO2peak (ES= 0.78). CONCLUSION: Successive days of simulated team sport exercise decreases markers of next-day performance capacity with no effect of protein timing on acute recovery. However, practical VIT increases muscle strength and aerobic capacity in as little as 5 days with the latter potentially enhanced by immediate post-exercise protein consumption.